Strength abilities in sports swimming: a systematic review - Nadobnik, J.; Wiazewicz, A. (Acta Kinesiologica, 2021)
Strength training is an important part of the preparation of competitive athletes. The subject of interest of the scientists connected of sports swimming was the level of strength ability of the competitors practising this sport and the influence of this ability on the final sports result. The purpose of this review is to describe and consider the impact of strength training of the shoulder muscles in sports swimming. A literature review was conducted in Embase, Medline PubMed, DOAJ, EBSCO and Google databases. Basic search terms are: training in sports swimming, strength tests, evaluation of muscle properties, rotation of the arm, strength measurement methods. Results: 235 results were found and 148 professional publications were selected and analysed. A thorough review of scientific publications indicates that strength parameters of the shoulder girdle muscles played a very important role on the sports performance of swimmers. The programmes combining swim training with 'on land' strength improvement or electrical stimulation are more effective than swim training alone. Significant fatigue of the rotator muscles can impair shoulder stability and result in injury. Increased strength in the internal rotation movement may result pathological conditions of the shoulder.